Effects of antibiotics on Staphylococcus aureus biofilm formation associated with Peri-implantitis - Aseel Al-Karawi; Abdulhameed Hameed; Sally Da'aj; Zeyad Abed (University Library System, University of Pittsburgh, 2023)
One hundred and twenty specimens were collected from patients with Peri-implantitis in the period from August 2022 until September 2022 from Baquba specialized dental center, in the province of Diyala. The goal of this work was to estimate the frequency of Staphylococcus aureus and their ability to produce biofilms associated with Peri-implantitis. Also, we aimed to assess the anti-biofilm property of Ciprofloxacin and Amoxicillin/clavulanic acid on Staphylococcus aureus. The result showed growth of Staphylococcus aureus in twenty isolates (16.6%), and 95% of the Staphylococcus aureus isolates had the ability to produce biofilms. The results indicate that the minimum inhibitory concentration (MIC) of Ciprofloxacin for Staphylococcus aureus was 32 to 512 μg/ml with the sub-MIC 16 to 256 μg/ml. The MIC for Amoxicillin/clavulanic was 8 to 512 μg/ml, and the sub-MIC 4 to 256) μg/ml. Ciprofloxacin and Amoxicillin/clavulanic acid had the ability to decrease biofilm formation and Amoxicillin/clavulanic acid was more effective than Ciprofloxacin.